밥맛이 우수한 경기지역 적응 조생종 벼 ‘정드림’ - 장정희(Jung-Hee Jang); 최병렬(Byoung-Rourl Choi); 원태진(Tae-Jin Won); 이지혜(Ji-Hye Lee); 이종형(Jong-Hyeong Lee); 한상욱(Sang-Wook Han); 장재은(Jae-Eun Jang); 서재순(Jae-Soon Seo); 지정현(Jung-Hyeun Ji); 박인태(In-Tae Park); 최해춘(Hae-Chun Choi); 김광호(Gwang-Ho Kim) (Korean journal of breeding, 2021)
‘Jungdream’ is an early maturing, high-quality rice cultivar developed in 2017 by the crop breeding team at Crop Research Division,GARES, Hwaseong, Korea. ‘Jungdream’ was first developed in 2008 from crossing a medium-late maturity cultivar ‘Chilbo’ and an early maturitycultivar ‘Ungwang’. The heading date of this cultivar is July 28thin the Gyeonggido Province. Its culm length is 63 cm, and it has 19 paniclesper hill and 82 spikelets per panicle. It is a medium-small grain brown rice cultivar with a 1000-grain weight of 20.6 g. Its cold toleranceis lower than that of ‘Hwaseong’, which is the standard cultivar in the central region, as is its degree of lodging tolerance. ‘Jungdream’ isresistant to rice blast and stripe virus diseases but is susceptible to bacterial leaf blight and other viral diseases and pests. The appearance ofmilled ‘Jungdream’ rice is clear, and its amylose content is 16.5%, which is lower than that of ‘Hwaseong’. The palatability of cooked ‘Jungdream’rice is better than that of ‘Chucheong’, which is the main cultivated crop in Gyeonggido. Its milling ratio is 75.0%, which is lower than thatof ‘Hwaseong’. The yield of milled ‘Jungdream’ rice was 5.42 MT/ha in the local adaptability tests during standard cultivation in four regionsfrom 2015 to 2017. ‘Jungdream’ is highly adaptable to the environmental conditions in the Gyeonggido Province (Registration No. 8236). KCI Citation Count: 0